2013
DOI: 10.1038/emboj.2013.194
|View full text |Cite
|
Sign up to set email alerts
|

Gene promoters dictate histone occupancy within genes

Abstract: Spt6 is a transcriptional elongation factor and histone chaperone that reassembles transcribed chromatin. Genome-wide H3 mapping showed that Spt6 preferentially maintains nucleosomes within the first 500 bases of genes and helps define nucleosome-depleted regions in 5 0 and 3 0 flanking sequences. In Spt6-depleted cells, H3 loss at 5 0 ends correlates with reduced pol II density suggesting enhanced transcription elongation. Consistent with its 'Suppressor of Ty' (Spt) phenotype, Spt6 inactivation caused locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 64 publications
18
39
0
Order By: Relevance
“…It is speculated that these effects of Spt6 are mediated through alterations in chromatin. Consistent with this hypothesis, Spt6 is a histone chaperone capable of assembling nucleosomes on naked DNA templates in the presence of topoisomerase I (22) and is involved in preventing loss of histones through transcribed regions (25,27,(40)(41)(42)(43).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…It is speculated that these effects of Spt6 are mediated through alterations in chromatin. Consistent with this hypothesis, Spt6 is a histone chaperone capable of assembling nucleosomes on naked DNA templates in the presence of topoisomerase I (22) and is involved in preventing loss of histones through transcribed regions (25,27,(40)(41)(42)(43).…”
mentioning
confidence: 56%
“…Spt6 participates in shaping the chromatin structure of Pol II-transcribed genes. Mutation of SPT6 can lead to depletion of histones H3 and H4 in actively transcribed regions and the inability to di-and trimethylate lysine 36 on his-tone H3 (14,27,40,41,43,59). Therefore, we asked whether changes in chromatin structure might account for the observed effect of Spt6 on Pol I transcription initiation.…”
Section: Spt6 Associates With Rdna and Is Essential For Rrna Synthesismentioning
confidence: 99%
“…Increasing levels of Tyr1 phosphorylation toward the 3= end then stabilizes Spt6-Pol II CTD interaction via the tSH2 domain. A recent study showed preferential loss of histones from the 5= ends of the transcribed genes in Spt6-depleted cells (16). We speculate that Spt6 recruitment by Ser2 phosphorylation is important for regulating histone occupancy near the 5= ends.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of Spt6 in yeast (Saccharomyces cerevisiae) causes a widespread reduction in histone H3 primarily from the 5= ends of transcribed genes, indicating the importance of Spt6 in maintaining histone occupancy (16). One of the effects of losing Spt6 function is altered gene expression and activation of intragenic cryptic transcription (17)(18)(19).…”
mentioning
confidence: 99%
“…A similar promoter modulation of downstream histone positioning was recently shown in yeast. 60 This suggests that promoter occupancy regulates events that occur on chromatin domains that largely exceed the promoter region. How is this achieved?…”
Section: Discussionmentioning
confidence: 99%